The deuterated pyrazoloquinolinone targeting α6 subunit-containing GABAA receptor as novel candidate for inhibition of trigeminovascular system activation: implication for migraine therapy - Fan, Pi-Chuan; Chiou, Lih-Chu; Lai, Tzu-Hsuan; Sharmin, Dishary; Cook, James; Lee, Ming Tatt (Frontiers in Pharmacology, 2024)
The α6 subunit-containing GABAA receptors (α6GABAARs) are highly expressed in the trigeminal ganglia (TG), the sensory hub of the trigeminovascular system (TGVS). Hypo-GABAergic transmission in the TG was reported to contribute to migraine-related behavioral and histopathological phenotypes. Previously, we found that Compound 6, an α6GABAAR-selective positive allosteric modulator (PAM), significantly alleviated TGVS activation-induced peripheral and central sensitization in a capsaicin-induced migraine-mimicking model. Here, we tested whether the deuterated analogues of Compound 6, namely DK-1-56-1 and RV-I-29, known to have longer halflives than the parent compound, can exert a similar therapeutic effect in the same model. The activation of TGVS was triggered by intra-cisternal (i.c.) instillation of capsaicin in male Wistar rats.Centrally, i.c. capsaicin increased the quantity of c-Fos-immunoreactive (c-Fos-ir) neurons in the trigeminal cervical complex (TCC). Peripherally, it increased the calcitonin gene-related peptide immunoreactivity (CGRP-ir) in TG, and caused CGRP release, leading to CGRP depletion in the dura mater. DK-I-56-1 and RV-I-29, administered intraperitoneally (i.p.), significantly ameliorated the TCC neuronal activation, TG CGRP-ir elevation, and dural CGRP depletion induced by capsaicin, with DK-I-56-1 demonstrating better efficacy. The therapeutic effects of 3 mg/kg DK-I-56-1 are comparable to that of 30 mg/kg topiramate. Notably, i.p. administered furosemide, a bloodbrain-barrier impermeable α6GABAAR-selective antagonist, prevented the effects of DK-I-56-1 and RV-I-29. Lastly, orally administered DK-I-56-1 has a similar pharmacological effect. These results suggest that DK-I-56-1 is a promising candidate for novel migraine pharmacotherapy, through positively modulating TG α6GABAARs to inhibit TGVS activation, with relatively favourable pharmacokinetic properties.